Display Cards as Innovative Media to Improve Quran Reading Skills at RA Nurul Furqon Pasir Mulya - Ningsih, Wida; Warti; Wartiningtyas; Ningsih, Widya; Winarti (Journal of Media and Learning Technology, 2025)
This study aims to examine the effectiveness of using demonstration cards as an innovative medium in improving the ability to read the Qur'an in group A at RA Nurul Furqon Pasir Mulya, Bogor City. The background of this study is based on the importance of the skill of reading the Qur'an from an early age, where conventional methods are sometimes less interesting for children. Therefore, innovation is needed in learning so that students are more motivated and active. The method used in this study is Classroom Action Research (CAR) which consists of two cycles. Each cycle involves the stages of planning, implementation, observation, and reflection. The subjects of the study were students of group A RA Nurul Furqon Pasir Mulya, with data collection techniques through observation, interviews, and documentation. The results of the study showed that the use of demonstration cards significantly increased students' interest and ability in reading the Qur'an. There was an increase in learning outcomes from the pre-cycle to cycle I, and increased again in cycle II. In addition, students seemed more enthusiastic and confident when participating in learning. In conclusion, demonstration cards have proven to be effective as an innovative medium in learning to read the Qur'an. The recommendation from this study is that teachers at RA Nurul Furqon and similar educational institutions adopt and develop creative learning media to improve the quality of Al-Qur'an learning for early childhood.